2013
DOI: 10.1007/s10750-013-1448-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological indices applied to benthic macroinvertebrates at reference conditions of mountain streams in two ecoregions (Poland, the Slovak Republic)

Abstract: The study was carried out from 2007 to 2010 in two ecoregions: the Carpathians and the Central Highlands. The objectives of our survey were to test the existing biological index metric based on benthic macroinvertebrates at reference conditions in the high-and mid-altitude mountain streams of two ecoregions according to the requirements of the EU WFD and to determine which environmental factors influence the distribution of benthic macroinvertebrates. Our results revealed statistically significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 54 publications
(46 reference statements)
3
42
1
4
Order By: Relevance
“…The greatest separation between HER for the three wiSD groups underlined the importance of using both levels of site classifications in evaluating physico-chemical differences between sites. Indices and metrics are generally used as a proxy of water quality and of structure of macroinvertebrate assemblages (AQEM consortium, 2002;Lewin et al, 2013;Manfrin et al, 2013). The LUI output confirms that HER15 sites showed the highest anthropic impact, the opposite for HER13, confirming the PCA scatter plot.…”
Section: Discussionsupporting
confidence: 53%
“…The greatest separation between HER for the three wiSD groups underlined the importance of using both levels of site classifications in evaluating physico-chemical differences between sites. Indices and metrics are generally used as a proxy of water quality and of structure of macroinvertebrate assemblages (AQEM consortium, 2002;Lewin et al, 2013;Manfrin et al, 2013). The LUI output confirms that HER15 sites showed the highest anthropic impact, the opposite for HER13, confirming the PCA scatter plot.…”
Section: Discussionsupporting
confidence: 53%
“…To conclude, the same environmental variables reflecting geology, geography or hydrology were the most important (statistically significant) and structuring the mountain stream communities both in the reference and human-impacted sites in these Ecoregions. The importance of geology, geography and hydrology was not displaced by the other factors such as water pollution when affected by human activities (Lewin et al, 2013(Lewin et al, , 2014. However, our previous studies showed that severe physical habitat modifications (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…These rivers are located at the highest altitudes, and their river channels are characterised by the greatest slopes, and related to that, the most dynamic flow and the coarsest-grained riverbed material. Water flowing in such rivers is most depleted in terms of its ion composition, and its pH is close to neutral (Lewin et al, 2013). Considerable specificity was also found for Carpathian calcareous rivers, which in terms of the water's physical and chemical parameters showed a strong dependence on substrate geology, being characterised by high total hardness, alkalinity, conductivity and pH.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Six versions of BMWP and three versions of ASPT were applied to determine the water quality of this stream. There have been many different successful adaptations of the BMWP and ASPT indices to countries other than the UK (AlbaTercedor and Sanchez-Ortega, 1988;Jacobsen, 1998;Ferreira et al, 2004;Czerniawska-Kusza, 2005;Roche et al, 2010;Kazancı et al, 2013;Lewin et al, 2013). It was found that the most appropriate indices for the physical and chemical indices are BMWP (original version) and ASPT (original and Czech versions) among all indices used in the current study.…”
Section: Discussionmentioning
confidence: 76%